The Effectiveness of Mindfulness Training on Cognitive Flexibility and Assertiveness in Individuals with Substance Use Disorder - Afzalian, Sepideh; Alizadeh Gharebaghi, Babak; Alishah, Moghaddeseh; MirAbdallahi, Zahra; Ahmadi, Maryam (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effectiveness of mindfulness training on cognitive flexibility and assertiveness among individuals with substance use disorder in the city of Sari.Methods and Materials: The present study employed a quasi-experimental design with a pretest–posttest structure and a non-equivalent control group. The statistical population consisted of all male opioid substance users aged 20 to 50 years who had active records in five addiction treatment centers in Sari during 2025. After administering the Cognitive Flexibility Questionnaire, 30 individuals who obtained scores lower than the cutoff point of 70 were selected through simple random sampling and randomly assigned into an experimental group (n = 15) and a control group (n = 15). Data collection instruments included the Cognitive Flexibility Questionnaire developed by Dennis and Vander Wal (2010) and the Assertiveness Questionnaire developed by Cutler and Guerra (1976). The experimental group participated in eight 60-minute mindfulness training sessions based on the protocol of Kabat-Zinn (2003), whereas the control group received no intervention. Data were analyzed using descriptive statistics, multivariate analysis of covariance, and univariate analysis of covariance through SPSS version 22.Findings: The findings indicated that the assumptions underlying multivariate analysis of covariance were satisfied, including normal distribution, homogeneity of variances, and homogeneity of regression slopes. The results of multivariate analysis of covariance demonstrated a statistically significant difference between the experimental and control groups in the combined dependent variables, F(2, 25) = 46.94, p < 0.01. Furthermore, univariate covariance analyses revealed that mindfulness training had a statistically significant effect on cognitive flexibility, F(1, 27) = 91.27, p < 0.01, η² = 0.778, and assertiveness, F(1, 27) = 65.51, p < 0.01, η² = 0.716. The results showed that mindfulness training produced greater effectiveness in improving cognitive flexibility compared with assertiveness.Conclusion: The findings of the present study demonstrated that mindfulness training is an effective psychological intervention for enhancing cognitive flexibility and assertiveness among individuals with substance use disorder.